Przydatność mieszanek trawiastych do rekultywacji gruntów bezglebowych z wykorzystaniem materii organicznej i popiołu = Suitability of some grass mixtures sown on various substrates containing ash and organic matter for lawns - Czyż, Henryk; Kitczak, Teodor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 2004-2005 the suitability of grass mixtures of the Poa pratensis, Festuca rubra, Lolium perenne, Festuca arundinacea and some waste mate-rials, low peat, bark of coniferous trees, compost, municipal waste water sediment straw, municipal grassland cuttings) for biological recultivation of ground without soil.Grass mixtures had been tested for their application as material for building lawns on sand. On poor media Festuca rubra produced good turf and good looking lawn, on media rich in nutrients the Lolium perenne type proved best, and as far as the productivity was concerned best were media containing municipal waste sediments.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); piasek; popiół; podłoża; masa organiczna; mieszanki traw; wygląd ogólny trawnika; sand; ash; substratum; organic matter; grass mixtures; total aspect of lawn